2011
DOI: 10.1162/jocn_a_00013
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Mechanisms of Word Learning in a Narrative Context: An Event-related Potential Study

Abstract: The vast majority of word meanings are learned simply by extracting them from context, rather than by rote memorization or explicit instruction. Although this skill is remarkable, little is known about the brain mechanisms involved. In the present study, ERPs were recorded as participants read stories in which pseudowords were presented multiple times, embedded in consistent, meaningful contexts (referred to as meaning condition, M+) or inconsistent, meaningless contexts (M−). Word learning was then assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 55 publications
(77 reference statements)
17
113
2
3
Order By: Relevance
“…Of course, if there were no distinction between episodic records and lexical records, then priming would have been obtained for both old and new items. Very similar results have been obtained in an eventrelated potential study by Batterink and Neville (2011), who showed that when newly leamed words were used as unmasked primes for semantically related target English words, an N400 effect was observed only when the task was episodic recognition and not when the task was lexical decision.…”
Section: Episodic L2 Hypothesissupporting
confidence: 83%
“…Of course, if there were no distinction between episodic records and lexical records, then priming would have been obtained for both old and new items. Very similar results have been obtained in an eventrelated potential study by Batterink and Neville (2011), who showed that when newly leamed words were used as unmasked primes for semantically related target English words, an N400 effect was observed only when the task was episodic recognition and not when the task was lexical decision.…”
Section: Episodic L2 Hypothesissupporting
confidence: 83%
“…This view is supported by a study by Batterink and Neville (2011), which looked at the N400 in semantic priming using newly learned words as primes. These authors found no behavioural or N400 priming effect immediately after a training task, which involved 10 exposures to the novel words in a story context.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, we found a double dissociation, with the N100 effect predicting syntactic learning but not comprehension, and the N400 correlating with comprehension but not syntactic learning. At a general level, the N400 is thought to index lexical access or semantic integration processes (Lau et al, 2008) and has been shown to be a sensitive index of semantic word learning (Batterink & Neville, 2011; McLaughlin et al, 2004; Mestres-Misse et al, 2007). Modulation of the N400 has also been reported during speech segmentation tasks that involve extracting new nonsense words from a continuous speech stream (Cunillera et al, 2006, 2009; Balaguer et al, 2007; Sanders et al, 2002).…”
Section: Discussionmentioning
confidence: 99%